2021
DOI: 10.3389/fchem.2021.636362
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Modelling-Based Drug Repurposing Approaches for SARS-CoV-2 Therapeutics

Abstract: The recent outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a devastating effect globally with no effective treatment. The swift strategy to find effective treatment against coronavirus disease 2019 (COVID-19) is to repurpose the approved drugs. In this pursuit, an exhaustive computational method has been used on the DrugBank compounds targeting nsp16/nsp10 complex (PDB code: 6W4H). A structure-based pharmacophore model was generated, and the selected model was escalated to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Among the five drugs KEDD identified, captopril and lisinopril are experimentally validated active compounds, whose binding affinity values are reported on PubChem [ 55 ]. Additionally, recent studies from the biomedical domain point out that vitamin C and enalaprilat also exhibit lowering effects on the protein [ 56 58 ], and an in silico work suggests that framycetin could be a potential ACE2 inhibitor [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the five drugs KEDD identified, captopril and lisinopril are experimentally validated active compounds, whose binding affinity values are reported on PubChem [ 55 ]. Additionally, recent studies from the biomedical domain point out that vitamin C and enalaprilat also exhibit lowering effects on the protein [ 56 58 ], and an in silico work suggests that framycetin could be a potential ACE2 inhibitor [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…RMSD records the deviations present between the initial structure and the final structure of the simulation run. Generally, a smaller deviation denotes a relatively stable structure [ 43 , 44 ]. In the current study, the RMSD for the six systems has projected to be stable below 0.3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Tobramycin and related molecules were also identified among candidate molecules for the S-RBD binding by drug repositioning analysis of drug molecules contained in the Drug ReposER database and molecular docking [79]. Pharmacophore-based drug repurposing analysis of the DrugBank compounds using docking screening and MD simulations revealed that framycetin, kanamycin, and tobramycin were among the promising candidate compounds to inhibit S protein and viral entry [80].…”
Section: Simulations Of the Sars-cov-2 Spike Trimers And Analysis Of ...mentioning
confidence: 99%